Correlation of the understanding environment concept with the character environment care for the biological education students - Sirtu Filaili Sari; Jamaluddin Jamaluddin; Mahrus Mahrus (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aims to determine the relationship between understanding the concept of the environment and the character of caring for the environment for students of the Biology Education S1 study program. This type of research is descriptive quantitative. The research was conducted online via google Forms on biology education students who have passed environmental courses. The results showed that the correlation value between the understanding of environmental concepts and the student's environmental care character (r) was 0.601, and the coefficient of determination (r2) was 0.3612, so it can be stated that there is a positive and significant relationship. In conclusion, there is a meaningful positive relationship between understanding the concept of the environment and the value of caring for the environment in students of the Bachelor of Biology Study Program. The contribution of environmental understanding to the character of caring for the environment is 36.12%, and the remaining 63.88% is outside the understanding of environmental concepts.